2015
DOI: 10.1007/s00203-015-1122-3
|View full text |Cite
|
Sign up to set email alerts
|

Extra-slow-growing Tardiphaga strains isolated from nodules of Vavilovia formosa (Stev.) Fed.

Abstract: Eleven extra-slow-growing strains were isolated from nodules of the relict legume Vavilovia formosa growing in North Ossetia (Caucasus) and Armenia. All isolates formed a single rrs cluster together with the type strain Tardiphaga robiniae LMG 26467(T), while the sequencing of the 16S-23S rDNA intergenic region (ITS) and housekeeping genes glnII, atpD, dnaK, gyrB, recA and rpoB divided them into three groups. North Ossetian isolates (in contrast to the Armenian ones) were clustered separately from the type str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
2
3
0
1
Order By: Relevance
“…In previous culture-based studies on soybean, it was shown that the lack of Nitrobacter may be due to either their slow growth as chemoorganotrophs or lack of NO 2 in the growth medium required for growth as chemolithotrophs. Similarly, Tardiphaga species have a growth rate of up to a 10-day doubling time in culture (63). Our study, along with other culture-independent studies, reports the presence of Nitrobacter and Tardiphaga within root nodules of soybean (34) and alfalfa plants (14,66).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In previous culture-based studies on soybean, it was shown that the lack of Nitrobacter may be due to either their slow growth as chemoorganotrophs or lack of NO 2 in the growth medium required for growth as chemolithotrophs. Similarly, Tardiphaga species have a growth rate of up to a 10-day doubling time in culture (63). Our study, along with other culture-independent studies, reports the presence of Nitrobacter and Tardiphaga within root nodules of soybean (34) and alfalfa plants (14,66).…”
Section: Resultssupporting
confidence: 77%
“…are genetically similar to the Bradyrhizobium spp. ( 61) and reported to have nodM and nodT genes (63), which are involved in signaling to the host plant and root nodule formation (64). Moreover, Tardiphaga isolates have been reported to have a role in the N cycle by carrying out dissimilatory nitrate reduction under anaerobic conditions (65).…”
Section: Resultsmentioning
confidence: 99%
“…The genetic basis for the low specificity of these isolates may be the similarity of their nod genes with representatives of different rhizobial families: Rhizobiaceae, Phyllobacteriaceae and Bradyrhizobiaceae . This data are in agreement with previous reports suggesting that symbiotic systems of relict plants can be formed with different rhizobial strains belonging to various taxonomic groups (Safronova et al, 2014, 2015a,b, 2017b).…”
Section: Resultssupporting
confidence: 93%
“…The species Vavilovia formosa growing in Western Asia and Caucasus mountains as well as Oxytropis triphylla, O. popoviana, O. tragacanthoides, Hedysarum zundukii, Astragalus chorinensis , and Glycyrrhiza uralensis originated from Baikal Lake region are known as Miocene-Pliocene relics (Malyschev, 2006; Sinjushin et al, 2009; Turuta et al, 2015). Information about strains isolated from root nodules of these plant species was recently published (Safronova et al, 2014, 2015a,b, 2017a,b). It was shown that these isolates belonged to different families of rhizobia ( Rhizobiaceae , Phyllobacteriaceae , and Bradyrhizobiaceae ) and new species Bosea vaviloviae and Phyllobacterium zundukense were described (Safronova et al, 2015a, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…GFAT controls the flow of glucose and limits the speed of the hexosamine biosynthetic pathway, thus controlling the formation of the final product [ 66 ]. The glucosamine-fructose-6-phosphate aminotransferase is encoded by nodM , an important nodulation gene with a role in the biosynthesis and secretion of Nod factors [ 67 ]. An experiment with mutant strains in the nodM and nodN genes of Rhizobium leguminosarum inoculated in hairy vetch [ Vicia hirsuta (L.) Gray] resulted in an average reduction of 30% in the number of nodules; however, no differences were observed in the formation of curled root hairs or infection threads, and the nodules formed fixed normal amounts of nitrogen [ 68 ].…”
Section: Discussionmentioning
confidence: 99%